Achieving Tunable Cold/Warm White-Light Emission in a Single Perovskite Material with Near-Unity Photoluminescence Quantum Yield - Zhou, Bo; Du, Aixuan; Ding, Dong; Liu, Zexiang; Wang, Ye; Zhong, Haizhe; Li, Henan; Hu, Hanlin; Shi, Yumeng (Nano-Micro Letters, 2023)
Single materials that exhibit efficient and stable white-light emission are highly desirable for lighting applications. This paper reports a novel zero-dimensional perovskite, Rb4CdCl6:Sn2+, Mn2+, which demonstrates exceptional white-light properties including adjustable correlated color temperature, high color rendering index of up to 85, and near-unity photoluminescence quantum yield of 99%. Using a co-doping strategy involving Sn2+ and Mn2+, cyan-orange dual-band emission with complementary spectral ranges is activated by the self-trapped excitons and d-d transitions of the Sn2+ and Mn2+ centers in the Rb4CdCl6 host, respectively. Intriguingly, although Mn2+ ions doped in Rb4CdCl6 are difficult to excite, efficient Mn2+ emission can be realized through an ultra-high-efficient energy transfer between Sn2+ and Mn2+ via the formation of adjacent exchange-coupled Sn–Mn pairs. Benefiting from this efficient Dexter energy transfer process, the dual emission shares the same optimal excitation wavelengths of the Sn2+ centers and suppresses the non-radiative vibration relaxation significantly. Moreover, the relative intensities of the dual-emission components can be modulated flexibly by adjusting the fraction of the Sn2+ ions to the Sn–Mn pairs. This co-doping approach involving short-range energy transfer represents a promising avenue for achieving high-quality white light within a single material. Highlights: 1 High-quality Sn2+/Mn2+-co-doped Rb4CdCl6 single crystals and powders were prepared and showed high-performance dual-emission white light with near-unity photoluminescence quantum yield. 2 Short-range and extremely strong interactions between Sn2+ and Mn2+ were observed that lead to an intriguing ultra-high-efficiency Dexter energy transfer process from adjacent Sn2+ ions to Mn2+ ions. 3 The dual-emission intensities were tuned flexibly by varying the fractions of Sn2+ and Sn–Mn pairs to balance their emission proportions for cold/warm white-light generation.